Europe's relations with Latin America : towards a bi-regional agenda for the twenty-first century (IRELA MadridES, 1999)
Addresses the political dimension of European-Latin American relations, the nature of European political interests in Latin America and the main policy determinants. Examines bi-regional economic relations and the future of EU-Latin America commercial links. Makes some recommendations on a bi-regional agenda for action in the early years of the next century.
Prepared for the Summit of the Heads of State and Government of the European Union, Latin America and the Caribbean... Rio de Janeiro 28-29 June 1999